New Keynesian Phillips Curves and potential identification failures: a Generalized Empirical Likelihood analysis - Martins, L. F.; Gabriel, V. J. (Journal of Macroeconomics, 2009)
In this paper, we examine parameter identification in the hybrid specification of the New Keynesian Phillips Curve proposed by Gali and Gertler [Gali, J., Gertler, M., 1999. Inflation dynamics: a structural econometric analysis. Journal of Monetary Economics 44, 195-222]. We employ recently developed moment conditions inference procedures, which provide a more efficient and reliable econometric framework for the analysis of the NKPC. In particular, we address the issue of parameter identification, obtaining robust confidence sets for the model's parameters. Our results cast serious doubts on the empirical validity of the NKPC.